English Language Proficiency And Its Challenges Among Students From Diploma Of Mechanical Engineering - Hasnizam Bin Hasan; Suzilawati Binti Iberahim (Indonesian Journal of Education Methods Development, 2019)
21st century education (PA-21) aims to create integration between Malaysia’s multi races, ethnicities and building respect toward cultural, religion and racial differences. English language mastery among students in executing the 21st century education is very important so that they can communicate and collaborate with others. Despite that, English language usage among students is hard to reach its target due to psychological and attitude barrier. Through this research, it is hope to identify the challenges in English language usage among Diploma of Mechanical Engineering students and two factors were identified which are psycholinguistics and sociolinguistics. Psycholinguistic focuses on the study of attitude, personality and motivation towards the taught language while sociolinguistic focuses on the student’s family background towards their language learning and mastery. Questionnaire and observation are the methods used in gaining information from 72 students’ respondents. Research data is analysed descriptively using SPSS. The end results shows that both psycholinguistics and sociolinguistics factor is related to each other where mostly challenges comes from applied linguistics factor. Advices are given to the respective lecturers in facing the English language usage challenges and in order to raise their learning motivation so that they can stand to survive the 21st century education (PA-21) challenges.